TRANSFORMASI DIGITAL EVALUASI AKADEMIK MELALUI SOSIALISASI DAN PENDAMPINGAN APLIKASI UJIAN BERBASIS KOMPUTER DI MA NURUL IHSAN BATURUSA - Zalliman, Iski; Rozani, Muhammad; Munir, Misbahul (Jurnal Abdi Insani, 2025)
The development of information and communication technology (ICT) has had a significant impact on various aspects of life, one of which is the world of education. In the field of education, there has been a significant change, namely the use of digital technology in the academic evaluation process, especially in the implementation of exams in schools. In the current digital era, the use of computer-based testing (CBT) applications is a modern, effective and efficient solution to support the academic evaluation system in learning. An innovative digital solution through the use of digital technology is needed to support the academic evaluation process at MA Nurul Ihsan Baturusa. The method used includes several stages, starting from problem identification, solution design, to implementation and evaluation of activities in the field. The socialization and mentoring activities for the implementation of the computer-based testing application carried out at MA Nurul Ihsan Baturusa went very well and received a positive response from all parties at MA Nurul Ihsan. This activity yielded several important achievements, demonstrating a transformation in the academic evaluation system within MA Nurul Ihsan. The socialization and mentoring activities for the implementation of the computer-based exam (CBT) application at MA Nurul Ihsan Baturusa were carried out successfully and successfully achieved the goals envisioned by the PKM team. Through a participatory approach, this activity improved teachers' and staff's understanding of digital evaluation technology and increased MA Nurul Ihsan's readiness to adopt a computer-based exam system.